1989
DOI: 10.1007/bf02333617
|View full text |Cite
|
Sign up to set email alerts
|

Ethmoidal meningioma revealed by transient global amnesia

Abstract: A patient in whom transient global amnesia (TGA) led to the diagnosis of an ethmoidal meningioma is described. One year after neurosurgery, the patient showed an impairment of long-term memory, without any clinical or neuroradiological sign of relapse. We suggest that TGA may express a preexisting subclinical impairment of memory neuronal systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…The findings, including the current case, amounted to 20 examples (table 2) [6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23]. This has extended the previous narrative reviews of TGA and tumour by Dinca et al [23] and Daniel [24].…”
Section: Case Reportsupporting
confidence: 76%
See 1 more Smart Citation
“…The findings, including the current case, amounted to 20 examples (table 2) [6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23]. This has extended the previous narrative reviews of TGA and tumour by Dinca et al [23] and Daniel [24].…”
Section: Case Reportsupporting
confidence: 76%
“…Many of the reports [7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19] predated widely accepted clinical diagnostic criteria for TGA [4], and for this reason, some cases might be excluded as not conforming to criteria. For example, in one case, the amnesic episode lasted more than 24 h [7], and in another, progressive memory problems followed a generalised tonic clonic seizure [11]; in yet another case, the patient was reported to have 6 episodes of TGA and on examination had bilateral papilloedema [16] (criticised as unlikely to be TGA by Hodges [29]).…”
Section: Case Reportmentioning
confidence: 99%
“…The presence of a hippocampal lesion allows the condition to be diagnosed with confidence, but in patients without discernible hippocampal lesions, a different etiology leading to the amnestic syndrome cannot be ruled out. It should also be acknowledged that TGA could be determined by the reported brain lesions other than hippocampal high signal intensities [25,26,27,28,29]. Agosti et al [30] suggested that TGA should be classified as ‘primary TGA’ or ‘TGA with structural brain lesions’, but the cited authors reported that both subtypes had comparable clinical features and were clinically indistinguishable.…”
Section: Discussionmentioning
confidence: 99%
“…Any cognitive disability seems to be more likely with attention and spatial abilities and with multiple-episode patients. Of course, without a pre-TGA memory evaluation, one cannot rule out TGA as a symptom of a preexisting subclinical memory impairment (Cattaino, Pomes, Querin, & Cecotto, 1989). Although there are sufficient indications of a permanent memory dysfunction in some TGA patients (i.e., those with multiple episodes), a definitive answer awaits further investigation.…”
Section: Number Of Patients 16 R ------------------------------mentioning
confidence: 99%